ANALISIS ASUHAN KEPERAWATAN KELUARGA MELALUI PENDIDIKAN KESEHATAN DENGAN METODE SING AND VIDEO BASED LEARNING (SI VIBAL) PADA KELUARGA ANAK USIA SEKOLAH - Anggia Nur 'Ardhia Safitri (2023)
The family is connected by marriage, adoption, or birth, as well as by the process of family development. The family process is currently experiencing the longest period of time and requires the assistance of others. At this point, health issues can arise. This study aimed to help people learn more about clean and healthy behavior (PHBS) by giving them health education counseling using singing and video-based learning (Si ViBaL). The first step was to check how much PHBS knew, thought, and did. Then, we taught them about health using the Si ViBaL method in three meetings. The results of this study on PHBS health education using the Si ViBaL method in managed patients showed an increase in knowledge from 54.4% to 90.9% and in attitude and behavior from 45.4% to 90.9%. In their resumes, patients showed an increase in knowledge from 63.6% to 100% and in attitude and behavior from 45.4% to 90.9%. This study shows that PHBS health education with singing and video-based learning (Si ViBaL) increases PHBS knowledge, attitudes, and behavior among school-age children.